Proceedings of the 3rd International Workshop on Systems and Network Telemetry and Analytics 2020
DOI: 10.1145/3391812.3396274
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection Improves Tree-based Classification for Wireless Intrusion Detection

Abstract: With the growth of 5G wireless technologies and IoT, it become urgent to develop robust network security systems, such as intrusions detection systems (IDS) to keep the networks secure. These IDS systems need to detect unauthorized access and attacks in real-time. However, most of the modern IDS are built based on complex machine learning models that are time-consuming to train. In this work, we propose a methodology using the SHapley Additive exPlanations (SHAP) in combination with tree-based classifiers. SHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The authors in [5] perform feature selection as a first step for tree-based classification of normal and malicious wireless traffic. Initially, they removed features that have zero values for at least 99% of the instances.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors in [5] perform feature selection as a first step for tree-based classification of normal and malicious wireless traffic. Initially, they removed features that have zero values for at least 99% of the instances.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, some contributions mention evaluation metric scores that seem questionable. For instance, each one of the works in [5,9,13,12] presents an almost equal Precision, Recall, F1, and Accuracy scores. Based on these results, it can be assumed that these works most probably employ a balanced dataset, and indeed this is the case with [5].…”
Section: E Comparison With Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same AWID dataset, Bhandari et al [1] showed that by selecting a subset of important features of size 10% of the initial set, the training time can be reduced by 4x, while improving the discriminating ability to identify attack instances. This study employed the SHAP method for feature selection and concluded that by selecting a small subset of the most important features, the algorithm is able to important patterns to discriminate between the "attack" instances and the "normal" instances.…”
Section: Introductionmentioning
confidence: 99%